Discriminating mental skills among adolescent elite and competitive soccer and volleyball players - Fathirezaie, Z.; Zamani Sani, S. H.; Ebrahimi, S.; Brand, S.; Jahanbakhsh, I.; Nazari, S. (Annals of Applied Sport Science, 2018)
Background. Mental skills are defined as a set of trainable mental abilities and methods that are held to underpin successful learning and performance. Objectives. The aim of the present research was to study and compare the mental skills of adolescent elite and competitive volleyball and soccer players. Methods. The sample consisted of 100 players (54 elite soccer, 13 elite volleyball, 18 competitive soccer and 15 competitive volleyball) selected via a purposive sampling method. Data were collected using the Ottawa Mental Skills Assessment Tool-2 (OMSAT-2). Results. Elite and competitive volleyball players had higher scores for stress reactions than elite soccer players. In addition, elite soccer players had more self-confidence than competitive soccer and volleyball players. Also, competitive volleyball players had higher levels of fear than elite soccer players. There were no other significant differences in mental skills between soccer and volleyball players. Conclusion. It seems that adolescent volleyball players stand in more immediate need of learning strategies for coping with stress, fear and self-confidence management than soccer players. Results are discussed in terms of an athlete`s levels, the nature and characteristics of the sport and choking during performance.